PHY1106: Waves and Oscillators: Dr. Pete Vukusic Differentiating sine / cosine The sine / cosine functions differentiate using standard sets of rules: d (sin t ) = cos t dt d (cos t ) = − sin t dt d ( − sin t ) = − cos t dt d ( − cos t ) = sin t dt Slightly more complicated is sin (ωt) or sin (ωt + φ) etc. In these cases the expression within the sine or cosine is itself differentiated w.r.t the variable “t”, in addition to the sin or cos function itself: these are then multiplied together. d ( A sin ωt ) = ωA cos ωt and dt d ( A cos ωt ) = −ωA sin ωt dt since d (ωt ) = ω dt For a further example, if the sin / cos function is now a more complicated function of t say, notice how we still differentiate it (as well as the sin / cos itself) ; e.g. for sin (kt2) and cos (kt3) etc. [ ] d sin(kt 2 ) = 2kt. cos(kt 2 ) dt and [ ] d cos(kt 3 ) = −3kt 2 . sin kt 3 dt If the function has two variables in it, (as with some of the functions in our lecture course, e.g. y = y 0 sin(ωt − kx ) ), then the differentiation works in the same way; d ( y ) = ωy 0 cos(ωt − kx ) dt In general: d ( y ) = −ky 0 cos(ωt − kx ) and dx d df dg [f(g(x))] = × dx dx dx This means we differentiate the outside function, leave the argument of the outside function alone, and then multiply by the derivative of the inside function. For example; d df dg [cos(3x 2 + 1)] = × = − sin(3x 2 + 1) × 6 x = −6 x. sin(3x 2 + 1) dx dx dx Practice Problems: Complete the following (see PV or your tutor for solutions): d [Aω sin(ωt )] = dt d [A cos(ωt − kx )] = dx d [Aω cos(ωt − kx )] = dt d − A cos(ωt − kx ) = dt ω d dk c. sin(ka / 2 ) = (a / 2)